Social media in the marketing context a state of the art analysis and future directions - Plume, Cherniece J.; Dwivedi, Yogesh Kumar; Slade, Emma L. (Chandos Publishing, 2017)
Social media has provided endless opportunities for marketers, fuelling their desire to learn more about their consumers through this dynamic online environment. Yet many organisations are finding it difficult to create effective marketing strategies, making decisions that are based on research that is highly focused on the nature and boundaries of social media. The changing behaviour of consumers, variety of platforms and changing culture indicates that much of the research around this topic is still highly fragmented. Social Media in the Marketing Context: A State of the Art Analysis and Future Directions provides a comprehensive overview of the current literature surrounding social media and the marketing discipline, highlighting future development opportunities in both knowledge and practice
Includes bibliographical references and index
Keywords: PSYCHOLOGY / Social Psychology; Marketing; Social media; Social Media; Online-Marketing; Kundenanalyse